Life-Threatening Mediastinal Teratoma of Infant Requiring Emergency Surgical Removal - Piber, Nicole; Weichert, Wilko; Hörer, Jürgen; Ono, Masamichi (The Thoracic and Cardiovascular Surgeon Reports, 2022)
Background Teratoma is a tumor derived from fetal germ cells with aberrant differentiation.Case Description A 3-month-old infant with a mediastinal tumor was referred to our heart center. She presented with progressive dyspnea, cyanosis, and the need to be manually ventilated. The computed tomography scan displayed a huge tumor restricting the distal trachea including the bifurcation. An emergent operation was performed and the tumor was completely removed. Histological examination confirmed a mature teratoma.Conclusion In such life-threatening situation, the early detection and the immediate operation are very important for the management of rapidly-progressing mediastinal teratomas compressing the respiratory tract.
Keywords: mediastinal tumor; teratoma; infant